(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The future of any nation depends on its education policy. The process of economic, social and cultural development is created through education. Education in the nation is an important way for the development of the nation and to make the future of the nation bright, so the education policy should be planned for the future. Education policy is an important direction for the future sustainable development of a country. The policy of starting multi-disciplinary institutes will give renewed focus on each field like arts, humanities and this type of education will help students to learn and develop holistically. Thus, students will be equipped with a strong knowledge base. Education policy will be important after the 1984 policy before the Government of India announced the first education policy in the 21st century. Education policy is a transformative and effective tool for human life.